AN OVERVIEW OF THE ANTHROPOLOGICAL IMPLICATION OF HEIDEGGER?S PHILOSOPHY OF TECHNOLOGY IN THE CONTEMPORARY NIGERIAN SOCIETY - Ignatius Nnaemeka Onwuatuegwu, Sunday Chukwuma Ezeani (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Technology is premised on facilitating and bettering man?s existence in the world. It should benefit and not limit man?s existence. However, one observes that contrary to this ideal, technology has led, in no small degree, to the forgetfulness of man. On this note, this research will attempt to problematise these questions: to what extent is technology anthropocentric in our contemporary Nigerian society? Has technology succeeded in aiding man to actualise his full potential and authenticity? Has man?s utility of modern technology uplifted or delimited his praxical existence in the world, with people and the cosmos? How has the inauthenticity orchestrated by aimless ?calculative? borrowing of Western modern technologies instigated and sustained the technological poverty in Nigeria? These questions depict the problem that motivates this research. It is, therefore, poised to awaken Africans especially Nigerians from technological developmental stagnancy and uncreative imitation of Western technology to creative, intelligent and humanistic technological ingenuity and utility. In order to achieve the purpose of this study, we will adopt hermeneutical and phenomenological methods. Hermeneutics method will be used to interpret and analyze the thoughts of Martin Heidegger on technology. And with phenomenological method we shall bring to light the conditions of modern technology and man in the contemporary society.